Infradesnivel del segmento ST y neumotórax espontáneo izquierdo - Rico-Lozano, Jonathan Andrés (2024)
Spontaneous pneumothorax is a rare entity, and its association with electrocardiographic changes is infrequent. In these cases, the most frequent abnormalities are ST-segment elevation, T-wave inversion and poor R wave progression in precordial leads. We present the case of a 25-year-old man who experienced a left spontaneous pneumothorax secondary to a subpleural bleb. Upon admission, his electrocardiogram revealed ST-segment depression in the inferior leads and aVF. These findings resolved following management of pneumothorax through thoracotomy.